Comparison of extraction sites versus artificial defects with xenogenic bone substitute in minipigs - Constanze Steiner; Matthias Karl; Matthias W. Laschke; Peter Schupbach; Andrea Venturato; Angelines Gasser (Wiley, 2021)
Abstract Objectives The preclinical evaluation of bone substitutes is frequently performed in artificially created defects. However, such defects do not reflect the predominant clinical application of bone substitutes for socket preservation. Hence, the goal of this animal study was to compare the performance of a xenogenic bone substitute in extraction sites versus artificial defects. Material and Methods Four study sites each were created in the mandibles of four minipigs in the region of the third premolars and first molars, respectively. On one side, fresh extraction sockets were established while contralaterally trephine defects were created in healed alveolar bone. All sites were augmented using a particulate xenogenic bone substitute, covered by resorbable membranes and allowed to heal for 12 weeks. The amounts of new bone, non‐bone tissue and remaining bone substitute granules were quantified through histological and micro‐CT analysis. Comparative statistics were based on t‐tests for two samples and ANOVA with the level of significance set at α = 0.05. Results Histomorphometric data from only two animals could be quantitatively analyzed due to difficulty with identifying the surgical sites. The percentage of newly formed bone ranged between 53.2% ± 5.6% for artificial defects and 54.9% ± 12.4% for extraction sites. With the exception of ANOVA indicating a greater amount of non‐bone tissue in extraction sites as compared to artificial sites (p = 0.047), no statistically significant differences were observed. Micro‐CT scans showed patterns similar to the ones observed in histomorphometry. As extraction sites could be identified only in two micro‐CT reconstructions, quantitative assessment was not undertaken. Conclusions Despite the comparable performance of bone substitute material in artificial defects and extraction sites found here, the data gathered with this experiment was insufficient for showing equivalence of both approaches.